2022
DOI: 10.48550/arxiv.2204.12977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovering gravitationally lensed gravitational waves: predicted rates, candidate selection, and localization with the Vera Rubin Observatory

Abstract: The first secure detection of a gravitationally lensed gravitational (GW) will be a watershed moment, as it will bring together these two pillars of General Relativity for the first time. Accurate selection and interpretation of candidate lensed GWs is challenging for numerous reasons, including large sky localization uncertainties for most GW detections, the broad range of gravitational lenses spanning galaxy/group/cluster-scales in the dark matter halo mass function, and uncertainty in the intrinsic mass fun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 114 publications
(183 reference statements)
1
12
0
Order By: Relevance
“…The cluster RX J2129.6+0005 was the only cluster left from our search at p=0.876 corresponding to an area = 226.05 deg 2 . Furthermore, at 𝐷 300 Mpc, this detection is close to the peak of the predicted population of lensed BNS mergers in LVK's third run (Smith et al 2022). Following the GW trigger announcement, two GCN circulars confirmed the detection of a contextual neutrino by IceCube and a sub-threshold gamma-ray source by HAWC from a sky position offset from RX J2129.6+0005 (IceCube Collaboration 2019; HAWC Collaboration 2019).…”
Section: Gw191216_213338supporting
confidence: 52%
See 4 more Smart Citations
“…The cluster RX J2129.6+0005 was the only cluster left from our search at p=0.876 corresponding to an area = 226.05 deg 2 . Furthermore, at 𝐷 300 Mpc, this detection is close to the peak of the predicted population of lensed BNS mergers in LVK's third run (Smith et al 2022). Following the GW trigger announcement, two GCN circulars confirmed the detection of a contextual neutrino by IceCube and a sub-threshold gamma-ray source by HAWC from a sky position offset from RX J2129.6+0005 (IceCube Collaboration 2019; HAWC Collaboration 2019).…”
Section: Gw191216_213338supporting
confidence: 52%
“…theoretical surfaces corresponding to infinite magnification. Smith et al (2022) showed that the pseudo catastrophe of the singular isothermal lens and the fold catastrophe bracket the range of time delays measured to date for lensed quasars, and thus form a solid basis for predicting time delays for other lensed transients. We therefore adopt the following convenient scaling relations for lenses with an isothermal slope:…”
Section: Gw Progenitor Modelmentioning
confidence: 67%
See 3 more Smart Citations